2010
DOI: 10.1111/j.1600-0897.2010.00937.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Responses in the Male Reproductive Tract of Lipopolysaccharide Challenged Rats

Abstract: The increase in Spag11 and defensin mRNA in response to LPS administration demonstrates their importance in protecting the male reproductive tract during infection. Results of this study help to understand male reproductive tract innate immune defense mechanisms and to design novel peptide antibiotics to prevent sexually transmitted diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 56 publications
1
24
0
Order By: Relevance
“…Specific knock out of AR in Sertoli or Leydig cells caused male infertility with spermatogenic arrest and hypotestosteronemia [30][32]. Several earlier studies demonstrated that acute LPS challenge caused a marked decrease in serum T level in adult male mice and rats [33], [34]. In the current study, we investigated whether maternal LPS exposure decreased T production in male offspring.…”
Section: Discussionmentioning
confidence: 89%
“…Specific knock out of AR in Sertoli or Leydig cells caused male infertility with spermatogenic arrest and hypotestosteronemia [30][32]. Several earlier studies demonstrated that acute LPS challenge caused a marked decrease in serum T level in adult male mice and rats [33], [34]. In the current study, we investigated whether maternal LPS exposure decreased T production in male offspring.…”
Section: Discussionmentioning
confidence: 89%
“…In the LPS-induced rat model of epididymitis, the expression of ␤-defensin (Defb) 29, 41, and 42 did not change significantly after LPS treatment, whereas the mRNA levels of the other nine members were significantly decreased, including SPAG11E (14). Another report showed that LPS challenge induced the expression of Spag11 mRNA variants and defensins in the male reproductive tract of rats, followed by a concomitant increase in protein expression (13). These apparent differences might derive from the methods by which LPS was administered (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some human epididymal DEFBs, such as DEFB118 (formerly ESC42), SPAG11E (also known as Bin1b), and DEFB126, possess both antimicrobial and diverse functions in sperm fertility. Moreover, a previous study suggested that defensins might play roles in the protection against LPS-induced inflammation because the intraperitoneal injection of rats with LPS increased the production of Spag11 variants and major defensin expression in the male reproductive tract (13). However, in a rat model of epididymitis, LPS-induced epididymitis decreased the expression of epididymal ␤-defensins, disrupted SPAG11E expression, and resulted in the impairment of sperm motility (14).…”
mentioning
confidence: 97%
“…The effect of endotoxin challenge on Pate expression was investigated in vitro and in vivo following the methodology described earlier [42], [43]. For the in vitro experiments, caput, cauda and testis from adult rats were dissected and cut into two longitudinal halves.…”
Section: Methodsmentioning
confidence: 99%
“…LPS dose and site of injection was chosen based on previous reports [43]. Rats were sacrificed at 3, 6, 9, 15 and 24 h after LPS treatment.…”
Section: Methodsmentioning
confidence: 99%